A Note on the Homily In decem uirgines in the Codex Athous Koutloumousiou 11 - Gârbacea, Radu (The journal of theological studies, 2025)
According to the Pinakes database, managed by the Institut de recherche et d’histoire des textes, the manuscript Athous Koutloumousiou 11 is one of the earliest witnesses to the text of the pseudo-Chrysostomic homily In decem uirgines (CPG 4580). This short note shows that folios 295v-299v of the Athonite manuscript do not preserve this homily, but rather a reworking of an authentic Chrysostomic text.